3-Ethoxycarbonyl-1,4-benzodioxin-2-carboxylic Acid - Edoardo Armano; Alessandro Giraudo; Camillo Morano; Marco Pallavicini; Cristiano Bolchi (Molbank)
3-Ethoxycarbonyl-1,4-benzodioxin-2-carboxylic acid, a novel 2,3-disubstituted benzodioxin, was prepared from readily available 1,4-benzodioxin-2-carboxylic acid by lithiation at C(3) and a reaction with the electrophile ethyl chloroformate. The analytical characterization of the product was performed via IR, 1H-NMR, 13C-NMR, HRMS, and HPLC-UV. Due to the unsymmetrically disubstituted unsaturation, the obtained monoester of 1,4-benzodioxin-2,3-dicarboxylic acid is a building block of great potential in the synthesis of a variety of compounds containing the benzodioxin or benzodioxane scaffold.